The potential role of olive groves to deliver carbon dioxide removal in a carbon-neutral Europe: Opportunities and challenges. (September 2022) - Galán-Martín, Ángel; Contreras, María del Mar; Romero, Inmaculada; Ruiz, Encarnación; Bueno-Rodríguez, Salvador; Eliche-Quesada, Dolores; Castro-Galiano, Eulogio
Abstract: Carbon dioxide removal (CDR) will be a key component of the climate change mitigation efforts to achieve the carbon-neutrality goals. Hence, a comprehensive assessment of the CDR potential at national and local levels is crucial to identify regional opportunities and deploy practical actions timely. This study focuses on the potential function of olive agroecosystems in delivering CDR in the European Mediterranean countries. Relying on a geospatial assessment of existing olive groves (and associated residual biomass) combined with statistical, process systems engineering, and life cycle emissions data, the CDR potential considering five promising actions linked with the olive agroecosystems was here estimated. These actions are i) conservation measures protecting tree carbon sequestration, ii) agricultural practices increasing soil carbon sequestration, iii) biochar production and utilization, iv) biomass conversion routes coupled with carbon capture and storage (CCS), and v) development of bio-based and CO2 -based materials. Overall, the bottom-up assessment highlights the value of the olive groves, currently storing around 0.22 Gt CO2 -eq in standing trees and potentially sequestering 0.03 Gt CO2 -eq annually in soils. Moreover, exploiting the abundant biomass wastes in biorefineries coupled with CCS could deliver gigatonne-scale CDR while producing various value-added products, achieving above 0.01 Gt CO2 -eq per year only using prunings for biochar or power, while other pathways show lower potential (e.g., 0.52 MtCO2 eq yr −1 for fermentation). These results may promote the large-scale deployment of CDR actions, stimulate new policy initiatives to exploit opportunities associated with the olive groves, and ultimately contribute to the transition toward the net-zero targets. Graphical abstract: Image 1 Highlights: Carbon dioxide removal is unavoidable to achieve carbon neutrality goals. CDR opportunities linked with European olive groves and industries are identified. Natural CO2 sinks are 0.22 Gt in standing trees and potentially 0.02 Gt yr −1 in soils. Investigated biorefineries CCS pathways could deliver above 0.02 Gt yr-1 CO2 removed. CDR at gigaton-scale can be delivered in Europe, exploiting only olive biomasses.